Microempreendedor individual (MEI): Evoluç\~ao da legislaç\~ao, revis\~ao da literatura e temas para o debate - Graziela Ansiliero; Rogério Nagamine Costanzi; Ricardo Cifuentes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This discussion paper presents a narrative review (non-systematic) of the specialized literature, particularly the empirical approach covering the period 2009-2021, on selected aspects of the MEI. The results and impacts analyzed, which are not exhaustive, indicate points where the MEI would need to be amended to avoid increasing its adverse effects, while preserving its positive ones, also considering the recent shocks and economic crisis and the labor market transformations that took place in Brazil. Studies based on different methodological approaches point to positive impacts on the formalization of enterprises and favorable results on social security inclusion/coverage; offer little to none evidence of effects on labor income, although analyzes are limited by inadequacy or insufficient data; point to targeting issues, at least when considering the original profile defined as policy priority for the intervention; indicate that the incentive mechanisms designed appear to be sufficient to attract members/affiliated, but not to overcome the factors that determine informality, given the limited levels of compliance; and suggest that the pejotizaç\~ao phenomenon, still shrouded in contradictory signs and evidence, should remain a concern to be addressed. There are still many gaps to be filled by specialized literature.
Keywords: H51; H77; I18; 330; MEI; formalization; RGPS; pejotizaç\~ao phenomenon